Post tuberculosis treatment infectious complications - Hsu, Desmond; Irfan, Muhammad; Jabeen, Kauser; Iqbal, Nousheen; Hasan, Rumina; Migliori, Giovanni Battista; Zumla, Alimuddin; Visca, Dina; Centis, Rosella; Tiberi, Simon (International journal of infectious diseases, 2020)
•Patients with pulmonary tuberculosis (TB) are more susceptible to future lung disease and accelerated lung ageing.•Exacerbations of chronic obstructive pulmonary disease, bronchiectasis, and pneumonia are more frequent after pulmonary TB.•Colonization and infection with non-tuberculous mycobacteria (NTM) and Aspergillus fumigatus are common in individuals with a degree of pre-existing lung destruction or prior cavitary disease.•NTM and Aspergillus need to be considered in the differential diagnosis when patients present with symptoms following treatment of pulmonary TB in addition to TB recurrence or reinfection.•Thorough post screening, with radiology at treatment completion and smoking cessation, along with vaccination for influenza and pneumococcus, may help prevent future lung insults. Following greater attention and follow-up of patients with treated pulmonary tuberculosis (TB), it has emerged that infections are more likely to occur in this cohort of patients. This comes as no surprise, as pulmonary TB is a destructive process that leads to cicatrization, alteration of parenchyma, bronchiectasis, and scarring of the lung, with reduction of lung volumes and an impact on pulmonary function. In addition to relapse and re-infection with TB, other pathogens are increasingly recognized in post-TB patients. This paper serves as a summary and guide on how to approach the post-TB patient with new signs and symptoms of pulmonary infection in order to ensure optimal management and rehabilitation.